Management of late postoperative capsular bag distension syndrome - two year case series - Otrošinová, Marianna; Novák, Jan; Krásnik, Vladimír (European journal of ophthalmology, 2025)
INTRODUCTION: Late capsular bag distension syndrome (CBS) is a rare complication of the ^lcataract surgery. AIM: The aim is to present 9 cases with delayed presentation and describe their successful management with surgical approach. METHOD: A two-year retrospective review of 9 cases was undertaken. Anterior segment optical coherence tomography (AS-OCT) was used to confirm this diagnosis. Aspiration of the milky fluid with 26 gauge needle followed by capsular bag lavage was performed and aspirated fluid was examined. RESULTS: Patients showed signs of late CBS 6,56 ± 1,94 years after uncomplicated phacoemulsification with intraocular lens (IOL) implantation into the capsular bag. All 9 patients presented with a turbid fluid collection within the distended capsular bag. AS-OCT showed a hyper-reflective material in the space between the IOL and distended posterior capsule. CONCLUSION: Awareness of the manifestations of CBS and choice of the correct imaging modality may lead to regular diagnosis and successful treatment. Management with aspiration of the milky fluid and lavage of the capsular bag is technically safe and effective procedure. It has the advantage of microbial testing of the fluid. AS-OCT is useful tool to differentiate this condition clearly from IOL opacification and posterior capsule opacification.
Keywords: Syndrome; Male; pouzdro oční čočky; lidé středního věku; retrospektivní studie; senioři nad 80 let; Lens Implantation, Intraocular; Aged, 80 and over; Humans; Middle Aged; Phacoemulsification; senioři; zraková ostrost; mužské pohlaví; Female; fakoemulzifikace; Lens Diseases; optická koherentní tomografie; nemoci oční čočky; Aged; syndrom; implantace nitrooční čočky; ženské pohlaví; Retrospective Studies; Lens Capsule, Crystalline; Visual Acuity; Postoperative Complications; lidé; pooperační komplikace; Tomography, Optical Coherence